Failure Mode And Effect Analysis On Risk Management At An Oil And Gas Survey Company In Indonesia - Rustono, Rustono; Modesti Triasrini, Fransiska; Paniya, Paniya (Publisher Cv. Inara, 2023)
Asia is the second highest number of work accidents in the world after Africa. There are over 30% of major accidents experienced in the oil and gas industry triggered by inadequate maintenance. The fatal accidents in oil and gas accident increased from 2019 to 2022 in Indonesia. This qualitative study aims to analyze the risks that may occur in offshore oil and gas survey activities at Company X, an oil and gas survey company in Indonesia using Failure Mode and Effect Analysis (FMEA). Company X is a company that provides survey activities for oil and gas as the main service. Primary data are collected by interviewing the vessel manager, an Executive, and three employees involved in offshore oil and gas surveys. The FMEA steps are transcribing the answers, arranging them to make them easier to understand, providing a severity rating, setting the occurrence, detection rating, calculate the Risk Priority Number (RPN), prioritizing activities work that has highest RPN value, for determining long-term improvement strategies. The study reveals that the RPN for working accident turned out to be the highest from all risks which is 175 points, meaning that this risk has the highest ranking and need a mitigation as soon as possible. The recommended actions for this risk are regular maintenance for audits and inspections and upgrading FFA (Fire Fighting Appliances) and LSA (Life Saving Appliances) equipment.